Er-Xian Decoction Stimulates Osteoblastic Differentiation of Bone Mesenchymal Stem Cells in Ovariectomized Mice and Its Gene Profile Analysis - Shufen Liu; Jianhua Huang; Jing Wang; Yongjian Zhao; Sheng Lu; Yongjun Wang; Qin Bian (Stem Cells International)
We studied the bone mesenchymal stem cells (bMSCs) and gene profiles regulated by Er-Xian Decoction (EXD), a traditional Chinese herbal formula widely used for postmenopausal osteoporosis treatment. Six-month-old female Imprinting Control Region mice that underwent ovariectomy were treated with EXD. After 3 months, bone mass was evaluated by μCT and histological and immunohistochemical detection. The self-renewal and differentiation capacities of bMSCs were evaluated by colony-forming unit-fibroblastic, colony-forming unit-adipocyte, and alkaline phosphatase staining. In addition, the expression of 26991 genes of bMSCs ex vivo at 2 weeks after EXD-treatment or of bMSCs in vitro after exposure to conditioned serum from EXD-treated rats was measured and analyzed using NimbleGen Gene Expression Profiling and Cluster and pathway analysis. EXD treatment increased bone mass, elevating osteocalcin protein levels in vivo and facilitating the self-renewal and osteoblastic differentiation of bMSCs ex vivo. EXD rescued several gene expressions that were dysregulated by OVX. These genes overlapped and their functions were involved in ten pathways between ex vivo and in vitro experiments. EXD exerts an osteogenic effect on bMSCs in OVX induced osteoporotic mice. Our results contribute to further study of its molecular mechanism and traditional use in the treatment of postmenopausal osteoporosis.